The Relationship Between Knowledge, Attitudes, and Practices and the Incidence of Chronic Kidney Disease in Patients Aged 18-45 at Hajj Hospital Medan in 2025 - Syahruni, Maghfira; Lubis, Rahayu (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
Chronic Kidney Disease (CKD) is a non-communicable disease characterized by a gradual and irreversible decline in kidney function. According to WHO data, 843.6 million people worldwide were affected by CKD in 2021. In Indonesia, the prevalence of CKD has increased significantly, with 697.5 million cases and 1.2 million related deaths reported in 2019, and over 843.6 million cases in 2021. At Haji Hospital Medan, 4,012 CKD cases were recorded in 2024, with the majority of patients falling within the productive age group. This trend poses a threat to individuals’ quality of life and productivity within society. This study aims to examine the relationship between knowledge, attitudes, practices, and medical history with the incidence of CKD among patients aged 18–45 years at Haji Hospital Medan in 2025. A cross-sectional study design was employed, involving a total of 118 respondents selected using accidental sampling. Data were collected through structured interviews using a validated questionnaire. Bivariate analysis using the chi-square test revealed significant associations between knowledge (p = 0.010), attitudes (p = 0.003), practices (p = 0.015), and medical history (p = 0.010) with the incidence of CKD. Insufficient knowledge about CKD risk factors and prevention, negative attitudes toward healthy lifestyles, non-compliance with medical recommendations, and a history of illness contribute to the rising incidence of CKD in the productive age group. These findings highlight the need to enhance promotive and preventive health efforts, particularly targeting the productive age population, to raise awareness of the importance of CKD prevention and early detection.